Mandatory Mask-Wearing and Hand Hygiene Associated With Decreased Infectious Diseases Among Patients Undergoing Regular Hemodialysis: A Historical-Control Study - Jun-Jian Qin; Yan-Fang Xing; Jian-Hua Ren; Yong-Jian Chen; Ying-Fei Gan; Yan-Qiu Jiang; Jie Chen; Xing Li; Xing Li (Frontiers Media S.A., 2021)
Background: Infections are the second leading cause of death among patients undergoing hemodialysis. However, preventive measures against infectious diseases are limited and have not been made mandatory for patients.Objective: To investigate the incidence of infectious diseases before and during the coronavirus disease (COVID-19) pandemic.Design: A historical comparative study of a prospective cohort.Setting(s): February 1, 2015 to January 31, 2020 was defined as the period before the mitigative confrontation of the COVID-19 pandemic in China. The period from February 1 to June 29, 2020 was defined as the period of mitigative confrontation of the COVID-19 pandemic in China.Participants: A cohort of patients undergoing hemodialysis whose infectious disease episodes were documented prospectively in the hemodialysis unit of the Third Affiliated Hospital of Guangzhou Medical University since February 1, 2015.Methods: Mandatory mask-wearing and reinforced hand-hygiene education were implemented to prevent COVID-19 from January 23, 2020 in China. The incidence of infectious episodes, including catheter-related infection, digestive tract infection, upper respiratory tract infection (UTRI), pneumonia, and infection at other sites, were documented and compared in the periods before and during the pandemic.Results: The historical control group consisted of 157 patients, with 79 patients in the COVID-19 prevention group. The mask-wearing rate of patients increased from 1.5 to 100%. Hand sanitizer consumption increased significantly during the COVID-19 pandemic. The compliance rates of hand hygiene increased from 66, 75.5, to 55% in physicians, nurses, and other employees before the pandemic to 90.5, 92.5, and 76.5%, respectively. The incidences of UTRI and pneumonia decreased during the pandemic (p < 0.001). Notably, catheter-related and digestive tract infections also decreased during the pandemic (p = 0.003 and 0.034, respectively). A matched-pair study was conducted to further analyze the 79 individual changes in the incidences of infectious disease before and during the pandemic. As a result, the incidences of UTRI, pneumonia, catheter-related infections, digestive tract infections, and infections at other sites all decreased during the pandemic.Conclusions: The present study indicated an association between mandatory mask-wearing and reinforced hand hygiene education and decreased respiratory, catheter-related, and digestive tract infection episodes in the hemodialysis unit.